Synthesis and Antimicrobial Activity of a New Series of Thiazolidine-2,4-diones Carboxamide and Amino Acid Derivatives - Abd Alhameed, Rakia (Molecules, 2019)
Novel thiazolidine-2,4-dione carboxamide and amino acid derivatives were synthesized in excellent yield using OxymaPure/N,N′-diisopropylcarbodimide coupling methodology and were characterized by chromatographic and spectrometric methods, and elemental analysis. The antimicrobial and antifungal activity of these derivatives was evaluated against two Gram-positive bacteria (Staphylococcus aureus and Bacillus subtilis), two-Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and one fungal isolate (Candida albicans). Interestingly, several samples demonstrated weak to moderate antibacterial activity against Gram-negative bacteria, as well as antifungal activity. However, only one compound namely, 2-(5-(3-methoxybenzylidene)-2,4-dioxothiazolidin-3-yl)acetic acid, showed antibacterial activity against Gram-positive bacteria, particularly S. aureus.